Reflection on the Communication of Urban Image of Chaoshan Area in the Era of New Media - Fang Huan; Zhang Tian; Zhang Yanting (SHS Web of Conferences, 2023)
Since the “13th Five-Year Plan”, China has made remarkable achievements in the construction of new urbanization, and its development has also shifted from increment and expansion to a new stage dominated by stock renewal. In the tide of diversified construction of city, Chaoshan area with strong regional characteristics and cultural deposit has been frequently frustrated in shaping its urban image. Many untrue public opinions and rumors even appear on new media platforms and are widespread. How to effectively communicate the urban brand image of Chaoshan area and therefore promote regional economic development has become an aspiration of every Chaoshan person. In this paper, by collecting and analyzing questionnaires, we design a “CBIO” model. In order to improve communication effect of urban image of Chaoshan area, communication subjects should paid attention to key factors such as communication tactics, urban brand positioning and urban infrastructure construction.